ISOLATION OF NOVEL PARA-PENTYL PHENYL BENZOATE FROM MONDIA WHITEI.(HOOK.F.) SKEELS (PERIPLOCACEAE), ITS STRUCTURE, SYNTHESIS AND NEUROPHARMACOLOGICAL EVALUATION. - Bamigboye J, Taiwo; Josephine Y, Osasan; Olujide O, Olubiyi; Idris A, Oyemitan; Shakir A.M, Atoyebi; Mark R.J., Elsegood; Raymond C.F, Jones (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Mondia whitei L. (Hook. F.) Skeels (Periplocaceae) is a medicinal plant used locally in managing pain, fever, loss of appetite and as aphrodiasc in the South-Western states of Nigeria. However, the fruit is consumed habitually in the South-Eastern states of Nigeria, leading to speculation that it may possess some central nervous system effect but which has not been scientifically investigated, hence this study. Methodology: Fresh fruits of Mondia whitei were collected and identified by a taxonomist. They were chopped into small pieces and extracted with absolute ethanol. The crude extract was subjected to various chromatographic techniques to isolate a novel compound whose structure was elucidated from the analysis of the crystal data and by extensive use of spectroscopy. The structure was confirmed by synthesis. The compound was subjected to anxiolytic and sedative activity assay. Computational analysis of the receptor binding event of isolated compound at the gamma amino butyric acid A receptor was also evaluated. Results: The structure of the compound was elucidated as para pentyl phenyl benzoate. The neuropharmacological evaluation of the compound indicated significant (p<0.05) depression of the central nervous system. The binding characteristics of the compound to gamma amino butyric acid A receptors appears to be more favorable than those obtained for gamma amino butyric acid, chlorpromazine, benzamidine, and is comparable with the affinity obtained for pentobarbitone and diazepam. Conclusion These present data provide evidence for the role of para pentyl phenyl benzoate in the habitual consumption of the fruit as well as its central nervous system activities.